A graduate in the labour market – a partnership for problem solving - Łagowska-Cebula, Monika (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
Finishing education and entering the labour market is a key step in the life of every young person. At this point the individual departs from their well-known environment. In this environment many convictions are acquired and strategies to handle the requirements of the system are learnt. Even though these strategies do not always lead to the development of the individual, they give them a sense of security. These mechanisms probably become automated and cease to be a cause of stress (Rożnowski 2009: 21). The labour market, however, is a new environment which can cause some anxiety and lead to many stressful situations. The individual must find their feet in an environment where the consequences of failure to fulfil certain obligations can result in a significantly higher penalty than in the education system. The labour market consists of potential employees capable and willing to work and employers willing to hire workers (Szaban 2013: 15) and that is why, the lack of diligence and punctuality as well as the neglect of duty result in loss of employment and subsequent exclusion from that environment. Certainly, at certain stages of education, like for instance university, students can also be threatened with expulsion, but before it actually happens they have many more opportunities to rehabilitate themselves than most employees in the labour market. The labour market conditions which are encountered by young people are also important because they directly contribute to their living situation. Young adults who live with their parents are considered to be lazy and unwilling to rise to the challenge of self-reliance. However, most frequently it is the lack of financial resources to rent a flat (not to mention to purchase it) that is the reason for this situation. In 2012, the percentage of people in Poland aged 18 to 34 living with their parents was 60.2% and 27 – 48.1% in the EU (Central Statistical Office 2013: 11). The purpose of this article is to present the situation encountered by university graduates while seeking their first job. The present situation of the labour market in Subcarpathian Voivodeship, the assistance offered to former students by the District Employment Agency, and their opinion on this aid will be discussed.
Keywords: unemployment; labor market; social problem; partnership